Enhancing cataloguing skills with CAI tools using CoPAS to improve novice cataloguers bibliographic description for published conference proceedings - De Silva, S.M.; Zainab, A.N. (SAGE Publications (UK and US), 2001)
Reports results of a study, conducted with 27 third-year undergraduate students at the Faculty of Information Studies, MARA Institute of Technology, Shah Alam, Malaysia, to evaluate the effectiveness of CoPAS (Conference Proceeding Adviser System), an expert system adviser designed to train novice cataloguers in creating bibliographic descriptions for nine types of published conference proceedings. Two groups of students were involved: a control group, which was asked to provide bibliographic descriptions for nine types of conference proceedings using AACR2R; and an experimental group, which was asked to undertake similar tasks using CoPAS. Results indicated that the experimental group performed significantly better than the control group. Results also indicated that text knowledge can be reinforced with the use of a computer assisted system, allowing students to perform significantly better in specific cataloguing tasks. Students with longer experience in computer use found it easier to master the use of the system as well as to comprehend the content and flow of information presented.